2020
DOI: 10.12968/jowc.2020.29.sup9.s8
|View full text |Cite
|
Sign up to set email alerts
|

Use of a dual-layer amniotic membrane in the treatment of diabetic foot ulcers: an observational study

Abstract: Background: Despite advances in the treatment, fewer than half of diabetic foot ulcers (DFUs) heal in 12 weeks and 85% of non-traumatic amputations follow the development of a DFU. The search for treatment options continues. Placental-derived products have shown promise in the treatment of DFUs. This study investigates Artacent (Tides Medical, US), a unique amniotic patch containing two layers of amnion and its potential to increase growth factor delivery. Method: This observational analysis included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, the application of placental-derived products enhances dermal fibroblast proliferation and recruits mesenchymal stem cells to the injury site [ 24 ]. Multiple studies have suggested that the use of placental-derived products can improve DFU healing and the time to heal, which supports their effectiveness as adjuvant treatments [ 25 - 27 ].…”
Section: Adjuvant Treatmentmentioning
confidence: 99%
“…Furthermore, the application of placental-derived products enhances dermal fibroblast proliferation and recruits mesenchymal stem cells to the injury site [ 24 ]. Multiple studies have suggested that the use of placental-derived products can improve DFU healing and the time to heal, which supports their effectiveness as adjuvant treatments [ 25 - 27 ].…”
Section: Adjuvant Treatmentmentioning
confidence: 99%